West Spitsbergen fold and thrust belt: A digital educational data package for teaching structural geology. (February 2023) - Horota, Rafael Kenji; Senger, Kim; Rodes, Nil; Betlem, Peter; Smyrak-Sikora, Aleksandra; Jonassen, Marius O.; Kramer, Daniel; Braathen, Alvar
Abstract: The discipline of structural geology is taking an advantage of compiling observations from multiple field sites to comprehend the bigger picture and constrain the region's geological evolution. In this study we demonstrate how integration of a range of geospatial digital data sets that relate to the Paleogene fault and thrust belt exposed in the high Arctic Archipelago of Svalbard, is used in teaching in bachelor-level courses at the University Centre in Svalbard. This event led to the formation of the West Spitsbergen Fold and Thrust Belt and its associated foreland basin, the Central Spitsbergen Basin. Our digital educational data package builds on published literature from the past four decades augmented with recently acquired high-resolution digital outcrop models, and 360° imagery. All data are available as georeferenced data containers and included in a single geodatabase, freely available for educators and geoscientists around the world to complement their research and fieldwork with course components from Svalbard.